2022
DOI: 10.26434/chemrxiv-2022-n1g60
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learning Potentials for Metal-Organic Frameworks using an Incremental Learning Approach

Abstract: Computational modeling of physical processes in metal-organic frameworks (MOFs) is highly challenging. The intrinsic length and time scales often stretch far beyond the nanometer and picosecond range due to e.g. large spatial heterogeneities or complex phase transitions. Machine learning potentials (MLPs) can extend the applicability of density functional theory (DFT) towards such challenging systems, but the generation of a representative training set of atomic configurations still poses a major challenge. In… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…It was recently shown that a data-generation scheme relying on underlying DFT-based MD techniques is not very efficient. 283 During a regular MD run, subsequent structures are very much correlated, and thus, a strategy where training data are derived from underlying DFT-based MD simulations is not very efficient. In this case a lot of quantum-mechanical evaluations are performed which do not give substantial new information to train the MLP.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown that a data-generation scheme relying on underlying DFT-based MD techniques is not very efficient. 283 During a regular MD run, subsequent structures are very much correlated, and thus, a strategy where training data are derived from underlying DFT-based MD simulations is not very efficient. In this case a lot of quantum-mechanical evaluations are performed which do not give substantial new information to train the MLP.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
“…To circumvent this caveat, we proposed an active learning scheme in which an iterative procedure is used to train the MLP. 283 A first-generation MLP is trained based on a small set of underlying training data and then used in enhancedsampling MD simulations. When new portions of phase space are encountered which have not yet been seen, new DFT evaluations are performed to train the next iteration of the MLP.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
“…Consequently, theoretical studies are of high interest for the analysis and prediction of MOF properties 59 , and reliable and accurate interatomic potentials are urgently needed 60,61 . Accordingly, several MLPs for MOFs have been reported in the literature to date 33,62,63 . For our benchmark study, two types of HDNNPs are constructed based on either converged fragments providing bulk-like DFT reference forces, or making use of smaller fragments of about half this diameter yielding forces strongly differing from the bulk material.…”
Section: Introductionmentioning
confidence: 99%
“…61,62 Accordingly, several MLPs for MOFs have been reported in the literature to date. 33,63,64 For our benchmark study, two types of HDNNPs are constructed based on either converged fragments providing bulklike DFT reference forces, or making use of smaller fragments of about half this diameter yielding forces strongly differing from the bulk material. We show that in both cases HDNNPs of comparable quality can be obtained predicting reliable forces suitable for simulations of large systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, the trajectory is highly correlated in time and thus most of the expensive AIMD data does not contribute useful information for the training of the model. This selection has been approached in different ways from random sampling and manual selection to more data-driven procedures, 25,27,[34][35][36][37][38][39][40][41] with QbC being a particularly efficient method. QbC considers a set of candidate structures, in this case the whole AIMD trajectory, and iteratively builds up the training set.…”
Section: Introductionmentioning
confidence: 99%